The Determinants of Natural Resource Dependence among the GCC - Alrubaye, Ali Ayad Hasan; Abd Ghani, Judhiana; Kamarudin, Ainatul Aqilah; Al-Jubouri, Amir Makhif (Advances in Social Sciences Research Journal, 2025)
This study investigates the structural and macroeconomic determinants of natural resource dependence in the Gulf Cooperation Council (GCC) countries, a region historically reliant on hydrocarbon revenues for economic growth and fiscal stability. Drawing upon the Resource Curse Theory, the analysis explores the short and long-run impacts of human capital development, foreign direct investment, government debt, trade openness, inflation, and governance quality on resource dependence. Utilizing panel data from 2003 to 2023 for six GCC countries, the study employs advanced econometric techniques, including panel unit root and cointegration tests, as well as Pooled Mean Group, Mean Group, and Dynamic Fixed Effects estimators. The results confirm significant long-run relationships between several explanatory variables and natural resource dependence. Specifically, human capital, FDI, and governance quality exhibit robust negative effects, indicating their critical role in reducing reliance on natural resources. Conversely, trade openness and inflation are positively associated with resource dependence, reflecting continued export concentration in hydrocarbons and macroeconomic volatility. Government debt, while important from a fiscal perspective, does not show a statistically significant long-run effect. The short-run dynamics are largely insignificant, reinforcing the notion that structural transformation is a gradual process requiring sustained policy interventions. The findings highlight the importance of comprehensive diversification strategies grounded in education, institutional reform, and targeted foreign investment. Policymakers in the GCC must prioritize long-term development planning, enhance institutional effectiveness, and promote sectoral diversification to mitigate the economic risks associated with resource dependence. This study contributes to the broader literature on resource-based economies and provides empirical evidence to inform policy design in the context of ongoing transformation efforts across the GCC.